Yield Performance and Blast Susceptibility of SomeWheat (Triticum aestivum) Varieties in Jashore (The Agriculturists, 2018)
A trial was conducted during 2015-16 to 2017-18 at the Regional Agricultural Research Station (RARS) of Bangladesh Agricultural Research Institute (BARI), Jashore to select some tolerant varieties against wheat blast. Fourteen varieties including eight old varieties (Sonalika, Kanchan, Sourav, Gourab, Shatabdi, Sufi, Bijoy, Prodip) and six newly released varieties (BARI Gom 25, BARI Gom 26, BARI Gom 27, BARI Gom 28, BARI Gom 29 and BARI Gom 30) were evaluated. The experiments were non-replicated and were planted in two sowing dates, at optimum (mid November) and late (mid December) conditions. Three irrigations were applied, at crown root initiation (CRI), heading and grain filling stages. Plants of border rows were inoculated by Magnaporthe oryzae triticum (MoT) spores (104 conidia ml-1) for infection once per week from three weeks after sowing until primary infection was observed. The significantly higher grain yield was observed in 2016-17 (3505 kg ha-1) which was similar to 2017-18 (3448 kg ha-1) and the lowest was in 2015-16 (1680 kg ha-1). The higher grain yield was obtained due to the higher grains spike-1 (45 no.) and 1000 grain weight (36.6 g) and lower blast disease incidence (% blast index 18.1%). In all three years, there was heavy infection of wheat blast in late sowing condition (% blast index 40.7) compared to the optimum sowing condition (% blast index 1.4), resulting in very poor crop yield (1696 kg ha-1). Among the varieties, the variety Gourab produced the highest yield (3395 kg ha-1) which was similar to the newly released variety BARI Gom 28 (3196 kg ha-1) and BARI Gom 30 (3134 kg ha-1). In case of blast disease severity, old varieties were less infested with some exception in Sonalika and Kanchan. On the other hand, BARI Gom 25 and BARI Gom 26 were more susceptible (% blast index 35.3-36.5) to wheat blast compared to BARI Gom 28 and BARI Gom 30 (% blast index 20.2-22.5).The Agriculturists 2018; 16(2) 65-74